2013
DOI: 10.1016/j.spinee.2013.07.396
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function Following Adult Spinal Deformity Surgery: Minimum Two-Year Follow-Up

Abstract: Background:The literature regarding pulmonary function in adult patients with spinal deformity is limited, and the effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Generally, an approximate 5–10% increase of the PFT values was observed at 12 months after corrective surgery ( 25 ). A retrospective study conducted by Lehman revealed that adult patients with preoperative pulmonary impairment (FEV1 of < 65%) had an overall 2.7% improvement in pulmonary function at postoperative 2-year follow-up, which was significantly different from the decline in pulmonary function for all other patients ( 26 ). Therefore, we expected that the PFT results of our patients may be improved after correction and collected data to evaluate lung function at 2-year and 5-year follow-up postoperatively.…”
Section: Discussionmentioning
confidence: 95%
“…Generally, an approximate 5–10% increase of the PFT values was observed at 12 months after corrective surgery ( 25 ). A retrospective study conducted by Lehman revealed that adult patients with preoperative pulmonary impairment (FEV1 of < 65%) had an overall 2.7% improvement in pulmonary function at postoperative 2-year follow-up, which was significantly different from the decline in pulmonary function for all other patients ( 26 ). Therefore, we expected that the PFT results of our patients may be improved after correction and collected data to evaluate lung function at 2-year and 5-year follow-up postoperatively.…”
Section: Discussionmentioning
confidence: 95%
“…‘Pulmonary function’ is not covered with the proposed outcome set. ‘Pulmonary function’ appears to be an important relevant outcome for patients [ 25 ], and it has been demonstrated to deteriorate after complex ASD surgery [ 26 , 27 ], but it is unclear what this domain entails and how to operationalize it. Furthermore, other as yet unknown domains may also become relevant, such as sleep deprivation, for which new (validated and reliable) measurement tools may become available.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of spinal corrective surgery on pulmonary function in patients with ASD is more controversial than it is for patients with AIS. There is a significant decline in pulmonary function 2 years after surgery to correct ASD, but patients with preoperative pulmonary impairment had improved pulmonary function 26 . In the present study, we found no significant improvement of respiratory dysfunction 1 year after surgery.…”
Section: Discussionmentioning
confidence: 99%